COVID19 in children with cancer in low- and middle-income countries: Experience from a cancer center in Chennai, India. (4th November 2020) - Radhakrishnan, Venkatraman; Ovett, Jerin; Rajendran, Aruna; Kolluru, Saikrishna; Pai, Vishwajeeth; Gnanaguru, Vijay; Dhanushkodi, Manikandan; Kalaiyarasi, Jayachandran Perumal; Mehra, Nikita; Selvarajan, Gangothri; Rajan, Arun Kumar; Karunakaran, Parathan; et al.
Abstract: Crowded outpatient clinics and common wards in many hospitals in low and middle-income countries predispose children, caregivers, and health care workers to infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report on the clinical features and outcomes of 15 children with cancer at our center who tested positive for SARS-CoV-2. Five out of 15 patients were symptomatic, and one patient required intensive care and respiratory support. All the patients in the study have recovered from the SARS-CoV-2 infection without any sequelae and have resumed their cancer treatment.